KEBIJAKAN PEMERINTAH TERHADAP PERKREDITAN BANK DI MASA PANDEMI COVID-19 - Lontoh, Rietha Lieke; Tambajong, Helena Benedicta (Universitas Nurul Jadid, 2022)
Banks as credit providers provide opportunities for the public to meet primary and secondary needs through credit facilities and require debtors to repay debts within a certain period based on existing principles. The situation that occurred during the pandemic due to the COVID-19 outbreak whose spread became uncontrollable, caused market uncertainty so that it also affected the economic condition of the existing community where many employees and employees were laid off, so they lost their jobs and experienced problems in payment. credit. The purpose of this study was to determine the government's policy through the Financial Services Authority towards public credit during the pandemic. The research method used is a normative legal research method with data collection through literature study and qualitative analysis by considering the facts in the field. The conclusion is that the government provides interest rate relief, extends the period, reduces principal arrears, reduces interest arrears, adds financing credit facilities, and converts financing loans to maintain the value of the rupiah currency. This credit relaxation is very meaningful in providing concessions related to interest payments on credit debt. This can be used by people who experience credit arrears. The government in providing new policies during this pandemic must provide legal protection and certainty by requiring all banks to provide credit relaxation while prioritizing the bank's prudential principle, besides that the bank must also minimize the debtor's misunderstanding of the criteria and mechanism for providing stimulus. in the form of credit relaxation.